Comparative effectiveness of East Asian traditional medicine for treatment of idiopathic short stature in children: Systematic review and network meta-analysis - Boram Lee; Chan-Young Kwon; Soobin Jang (Integrative Medicine Research)
Background: Idiopathic short stature (ISS) is a common problem in children and causes many economic and social burdens. In Asian countries, East Asian traditional medicine (EATM) therapies are widely used for children with ISS. In this study, we compared and ranked various EATM therapies for the treatment of pediatric ISS using network meta-analysis. Methods: Randomized controlled trials that evaluated various EATMs for pediatric ISS were found through searching 14 electronic databases. The primary outcome was growth velocity (GV). The comparative effectiveness of the treatments was ranked based on the surface under the cumulative ranking curve (SUCRA) and the risk of bias was assessed. The quality of evidence was assessed using the Grading of Recommendations, Assessment, Development, and Evaluations approach. Results: Fourteen studies comprising 1,066 participants were included. HM plus GH showed statistically significant superiority over other EATM therapies including acupuncture (weighted mean difference (WMD) 3.20 cm, 95% confidence interval (CI) 0.40 to 5.99) and HM (WMD 3.70 cm, 95% CI 1.41 to 5.99) for improving GV per year, although there was no difference compared with GH alone (WMD 1.18 cm, 95% CI -0.27 to 2.63). SUCRA indicated that HM plus GH was the most effective therapy for increasing GV, followed by GH, HM plus acupressure, and HM. No serious adverse events were reported. Conclusion: For the treatment of ISS, HM plus GH might have a large beneficial effect and might be a better option than EATM therapies and GH alone. However, more long-term, high-quality trials are warranted to confirm the findings. Protocol registration: PROSPERO (https://www.crd.york.ac.uk/prospero/), CRD42020187160.